UJI PERFORMA MODUL PELTIER TIPE TEC1-12715 SEBAGAI SISTEM PENDINGIN PADA COOLBOX - Lusye Heni Maria Bonggoibo; Tobias T Tukan; Ishak Semuel Erari; Kwasti Kartono Kardiputra; Elohansen Padang (Jurnal Natural, 2025)
A Peltier module is a type of Thermoelectric Cooler (TEC) utilized in this study as the cooling system for a coolbox. The objective of this research is to analyze the cooling rate, the lowest achievable temperature, and the performance of the Peltier module by varying the number of modules and the cooling load. The experiment was conducted using variations in the number of Peltier modules (one and two) and variations in the cooling load an empty coolbox and a coolbox containing 1 liter of water. The results indicate that using two Peltier modules accelerates the cooling process and achieves a lower minimum temperature. The lowest temperatures recorded for the empty coolbox were 210C for one module and 19.80C for two modules. For the coolbox containing 1 liter of water, the lowest temperatures achieved were 22.90C for one module and 22.60C for two modules. An increase in the number of modules leads to a greater amount of heat extracted. The heat extracted by one Peltier module in the empty coolbox was 2882.4 J and 3270.1 J for two Peltier modules. In the coolbox containing 1 liter of water, the heat extracted was 22608.55 J for one module and 27418.9 J for two modules. This study also determined the Coefficient of Performance (COP) of the Peltier module system. The COP for the empty coolbox was 4.38% for one module and 3.66% for two modules. Conversely, the COP for the coolbox with 1 liter of water was 2.75% for one module and 2.31% for two modules. The highest COP recorded was 4.38% for one module and 3.66% for two modules, both occurring when the coolbox was empty coolbox (no load).